The use of the cultural competence assessment tool (ccatool) In community nurses: the pilot study and test-retest reliability - Vasiliou, Marios; Raftopoulos, Vasilios; Kouta, Christiana (My University, 2013)
Background: Nurses are responsible and accountable for their nursing practice and there is a need to be culturally and linguistically competent in all of their encounters. To be culturally competent community nurses should have the appropriate transcultural education. It is therefore important to assess the level of cultural competence of the community nurses, within their everyday practice. Aim: The aim of the article was the cultural adaptation of the cultural competence assessment tool based on Papadopoulos, Tilki and Taylor Model in a sample of Cypriot community nurses. Methodology: To explore the psychometric properties of the Cultural Competence Assessment Tool that has been distributed in a sample of 28 community nurses. Also, a pre and post-measurement has been applied as to assess the test-retest reliability of the tool. Results: The analysis has shown that the Cultural Competence Assessment Tool has good psychometric properties and it is easy to understand by the community healthcare professionals. Results showed that 60.7% disagreed that there is the same level of cultural competency with other European countries and 89.3% reported that assessment of their cultural competence is needed. Using the special analysis software for this tool, the pilot study showed that Cypriot community nurses have some degree of cultural awareness. Conclusion: Culturally competent care is both a legal and a moral requirement for health and social care professionals. Valuing diversity in health and social care enhances the delivery and effectiveness of care for all people, whether they are members of a minority or a majority cultural group. Using an appropriate tool for assessing cultural competence is very important and useful for health professionals to be culturally competence.
Keywords: Cultural competence; Transcultural nursing; Community nursing; Cultural competence models; Cultural competence tools